Discussion of Artificial Intelligence from an Artificial Reasoning Perspective - Raglin, Adrienne (Proceedings of the AAAI Symposium Series, 2026)
The advances in artificial intelligence are significant andrapid. Increased computational power, generative AI andlarge pretrained models are drivers of these advances.Artificial reasoning explores different reasoning paradigmsand how they can be used to enable artificial intelligentsystems with capabilities for tackling various tasks.Artificial reason-Ing also considers the human loop orhuman AI loop paradigm that highlights the notion that theroles of human and AI shift as AI gains new abilities. Thispaper discusses some of the ongoing questions that continueto move AI forward, particularly their ability to reason.